STYLE IN SONG LYRICS BERKELANA KE UJUNG DUNIA BY SUSILO BAMBANG YUDHOYONO (STYLISTICS ANALYSIS) - Erna Erpiana; Yumna Rasyid; Zuriyati Zuriyati (Universitas Indraprasta PGRI, 2019)
Abstrack. Style of language can be interpreted as an individual way of expressing ideas or characteristics of how individuals communicate. A politician has his own style, even the head of state, community leaders and even writers. The essence is that nothing is really the same in someone's style, both when speaking and writing. In stylistic studies it is often referred to as a linguistic approach to literature, because literature is inseparable from the medium of language. This paper will discuss the style of language in the lyrics of the song Berkelana ke Ujung Dunia by Susilo Bambang Yudhoyono. Song lyrics are considered to be the same as poetry, so the study of song lyrics is right using stylistic studies with the method of content analysis. The purpose of this study is to describe: (1) the style of words in the song Berkelana ke Ujung Dunia; (2) The sentence style in the song Berkelana ke Ujung Dunia; (3) Figure of speech in the song Berkelana ke Ujung Dunia.